Pengaruh Penerapan Model Pembelajaran Gambar Berurutan (Picture And Picture) Terhadap Keaktifan Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas VII SMP Negeri 4 Siborongborong Tahun Pembelajaran 2023/2024 (International Forum of Researchers and Lecturers, 2023)
The aim of this research is to find out whether the effect of increasing the learning activity of Christian religious education and the character of students who are taught using the sequential picture learning model (picture and picture) is higher than students who are taught without the sequential picture learning model (picture and picture) in class VII SMP Negeri 4 Siborongborong for the 2023/2024 academic year. This research uses a Posttest-Only Control type experimental method. The population is all VII SMP Negeri 4 Siborongborong for the 2023/2024 academic year, totaling 235 people. The sample was determined using a technique taken deliberately (purposive sampling) with the specified conditions that the experimental learning material was in that class, namely 35 students in class VII-2 as the experimental class and 35 students in VII-3 as the control class. The research instrument used 30 closed numbers. The t test used is the Separated Variance t test according to the test analysis requirements, namely n1=n2 and the variance of the two sample groups is homogeneous. The results of hypothesis testing obtained a value of t = 7.941> t table (α = 0.05; dk = n1 + n2-2 = 35 + 35-2 = 68) = t table 1.671, so H0 is rejected and Ha is accepted. This research concludes that there is an increase in the learning activity of Christian Religious Education and Characteristics of students who are taught using the sequential picture learning model (picture and picture) which is higher than students who are taught without the sequential learning model (picture and picture) in class VII of SMP Negeri 4 Siborongborong Year Learning 2023/2024.